Occupational exposures and cancer risk in commercial laundry and dry cleaning industries: a scoping review - Emma Ann Landskroner; Candace Su-Jung Tsai (BMC, 2023)
Abstract Background The laundry and dry cleaning industries are critical for maintaining cleanliness and hygiene in our daily lives. However, they have also been identified as sources of hazardous chemical exposure for workers, leading to potentially severe health implications. Despite mounting evidence that solvents like perchloroethylene and trichloroethylene are carcinogenic, they remain commonly used in the industry. Additionally, while alternative solvents are increasingly being utilized in response to indications of adverse health and environmental effects, there remains a significant gap in our understanding of the potential risks associated with exposure to these new agents. Methods This study aims to identify gaps in the literature concerning worker exposure to contemporary toxic chemicals in the laundry and dry cleaning industry and their associated carcinogenic risks. A scoping review of peer-reviewed publications from 2012 to 2022 was conducted to achieve this objective, focusing on studies that detailed chemical exposures, sampling methods, and workers within the laundry and dry cleaning sector. Results In this scoping review, 12 relevant papers were assessed. A majority (66%) examined perchloroethylene exposure, with one notable finding revealing that biomarkers from dry cleaners had significant micronuclei frequency and DNA damage, even when exposed to PCE at levels below occupational exposure limits. Similarly, another study supported these results, finding an increase in early DNA damage among exposed workers. Separate studies on TCE and benzene presented varied exposure levels and health risks, raising concern due to their IARC Group 1 carcinogen classification. Information on alternative solvents was limited, highlighting gaps in health outcome data, exposure guidelines, and carcinogenic classifications. Conclusion Research on health outcomes, specifically carcinogenicity from solvent exposure in dry cleaning, is limited, with 66% of studies not monitoring health implications, particularly for emerging solvents. Further, findings indicated potential DNA damage from perchloroethylene, even below set occupational limits, emphasizing the need to reevaluate safety limits. As alternative solvents like butylal and high-flashpoint hydrocarbons become more prevalent, investigations into the effects of their exposure are necessary to safeguard workers' health. This scoping review is registered with the Open Science Framework, registration DOI: https://doi.org/10.17605/OSF.IO/Q8FR3 .